Eudaimonia Happiness in Honorary Teachers in Elementary Schools of Rural Areas - Rahman, Syahnur; Hanurawan, Fattah; Macmudah, (International Conference on Sustainable Health Promotion, 2023)
This study aimed to explore the factors that contribute to eudaimonia happiness in honorary teachers in elementary schools of rural areas. This study uses a literature review approach from various journals related to happiness eudaimonia in honorary teachers in elementary schools in rural areas and can be applied to institutions that contribute to the research. The recommendation in this review literature is how happy primary school teachers who teach in rural areas